Interleukin 32 Promotes Foxp3+ Treg Cell Development and CD8+ T Cell Function in Human Esophageal Squamous Cell Carcinoma Microenvironment - Han, Li; Chen, Shiyu; Chen, Zheyi; Zhou, Bingqian; Zheng, Yingxia; Shen, Lisong (Frontiers in Cell and Developmental Biology, 2021)
Pro-inflammatory cytokine Interleukin-32 (IL32) is involved in infectious diseases and cancer, but what subtypes of immune cells express IL32 and its roles in tumor microenvironments (TME) have not been well discussed. In this study, we applied bioinformatics to analyze single cell RNA sequencing data about tumor infiltrating immune cells from esophageal squamous cell carcinoma (ESCC) TME, and analyzed IL32 expression in different immune cell types. We found CD4+ regulatory T cells (Treg cells) express the highest level of IL32, while proliferating T and NK cells expressed relatively lower levels. Knocking down of IL32 reduced Foxp3 and IFN expressions in CD4+ and CD8+ T cells, respectively. IL32 was positively correlated with Foxp3, IFN, and GZMB expression but was negatively correlated with proliferation score. IL32 may have a contradictory role in the tumor microenvironment such as it promotes IFN expression in CD8+ T cells which enhances the anti-tumor activity, but at the same time induces Foxp3 expression in CD4+ T cells, which suppresses the tumor immune response. Our results demonstrated different roles of IL32 in Treg cells and CD8+ T cells and suggested that it can potentially be a target for ESCC cancer immunosuppressive therapy.